Umbral ambiental para la concientización del medio ambiente, como un santuario para el nacimiento del Rio Bogotá y el Páramo Guacheneque por medio de una arquitectura sustentable. (2022)
In recent years, the moors in Colombia have been affected mostly due to global warming and activities carried out by the community in its greenest and most arborized areas such as agriculture, livestock and illegal mining. The approach of the architectural project aims to recompose and recover the ecological structure through the consolidation of a facility for awareness that allows and encourages the population to protect the source of the Bogotá River and the Guacheneque moor, in the municipalities of Villa Pinzón, Turmequé and Umbita Boyacá. To analyze this problem, studies of the intervention site were carried out and current problems were identified as a methodology to propose a specific solution through a project. In response, a design initiative is proposed that bets on the space of the moor as an environmental threshold for the awareness of the environment in the population, in order to improve the quality of public space, recover the environmental and landscape values ​​of the place. With the possibility of associating environmental recovery with the improvement of the quality of life.